Perancangan Aplikasi Augmented Reality Sebagai Media Pembelajaran Tata Surya Pada Sekolah Dasar Kelas 6 - Aslam Hadil Matin; Hari Widi Utomo (STMIK Budi Darma, 2023)
This research aims to build an Android application that uses Augmented Reality (AR) technology as a learning aid about the Solar System. The teaching methods currently used in grade 6 are considered less effective by many students because they use only explanatory theory textbooks and few simple media for practice. Therefore, this AR application is designed to blend virtual objects with physical objects naturally through a computerized process, so that it looks as if the virtual object is actually in front of the user and looks real. The purpose of this research is to develop an AR application that can increase the effectiveness of Solar System learning by providing students with an immersive visual experience. The development method used in this study is the Multimedia Development Life Cycle (MDLC). Application testing is carried out using Black Box Testing to ensure that all application features can run properly according to their functions. The pre-test results showed an average of 57, while the post-test results showed a significant increase with an average of 88. This shows that the use of AR applications in Solar System learning can significantly improve students' understanding. Thus, this AR application is considered an effective and efficient learning medium and is very interesting for users to use as a learning tool. The use of AR technology in learning can provide interactive and immersive learning experiences, increasing students' interest and understanding of the Solar System